Theorizing about resource integration through service-dominant logic. (September 2014) - Peters, Linda D.; Löbler, Helge; Brodie, Roderick J.; Breidbach, Christoph F.; Hollebeek, Linda D.; Smith, Sandra D.; Sörhammar, David; Varey, Richard J.
Resource integration, as it relates to value creation, has recently been a key aspect of the discussions about service-dominant (S-D) logic. However, the majority of research pays relatively little explicit attention to the process of theorizing and the epistomological and ontological assumptions upon which the theorizing process is based. This article addresses these issues. The processes that relate to theorizing and developing strong theory are discussed. We then examine how to conceptualize 'resources' and 'resource integration' following differing ontological and epistemological assumptions that guide the theorizing process. Research recommendations to help navigate through the finer details underlying the theorizing process and to advance a general theory of resource integration are developed.